2008
DOI: 10.1002/adfm.200701305
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Dipole Coupling and Depolarization in Self‐Assembled Monolayers

Abstract: Quantum mechanical and classical atomistic computational methods are used to simulate the chain‐length dependence of depolarization effects in S(CH2)n−1CH3 and S(CH2)n−1COOH self‐assembled monolayers on gold (111) surface. These calculations show that due to weak cooperative effects, the electrostatic properties of alkanethiol monolayers are well described by the gas phase dipole moments of the molecules. However, depolarization in monolayers with the molecules carrying head‐ and tail‐group dipoles, such as CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 57 publications
5
84
0
3
Order By: Relevance
“…Indeed, depolarization effects have been observed in several systems, both experimentally [74,75] and theoretically (for SAMs see, for example, References [58,59,76]), and have been described using equations analogous to Equation (2). [75,58] A more detailed analysis, however, reveals that this equation cannot be directly applied to SAMs; [70] as intermolecular distances are comparable to the lengths of the molecules, the point-dipole approximation no longer holds.…”
Section: Depolarization Phenomena In Dipolar Samsmentioning
confidence: 96%
“…Indeed, depolarization effects have been observed in several systems, both experimentally [74,75] and theoretically (for SAMs see, for example, References [58,59,76]), and have been described using equations analogous to Equation (2). [75,58] A more detailed analysis, however, reveals that this equation cannot be directly applied to SAMs; [70] as intermolecular distances are comparable to the lengths of the molecules, the point-dipole approximation no longer holds.…”
Section: Depolarization Phenomena In Dipolar Samsmentioning
confidence: 96%
“…Studies have shown that this simple classical model, based largely on parallel-plate capacitors, 251 gives quite accurate description of results from quantum mechanical calculations and experiments. [252][253][254][255][256][257] The necessary inclusion of a dielectric constant for the molecular layer in the above equation is due to the polarizability of the molecules. It has been shown that the effect of the depolarization of the molecular dipoles by the presence of other dipoles in the molecular layer can be accounted for by replacing in Eq.…”
Section: Dv¼mentioning
confidence: 99%
“…The charges on the atoms of the SAM molecules in the CE region are equal to the Mulliken charges of alkanethiols, obtained using B3LYP/6-31G(d), which ensures the consistency of electrostatic interactions in the system. 103 The short-range attraction between the quantum atoms and the classical atoms outside the QM cluster are described using the same potentials as in the CE (eq. 2).…”
Section: Computational Detailsmentioning
confidence: 99%
“…22,[24][25][26][27][28]97,103,[123][124][125][126] It has been demonstrated that the intramolecular electrostatic interactions in the monolayer lead to the redistribution of the electron density along the molecules (depolarization effect). This charge redistribution has a profound effect on the electrostatic potential both inside and outside the monolayer and determines the work function of the interface and the interaction of external molecules with the interface.…”
Section: Electrostatic Interactionsmentioning
confidence: 99%